Keanekaragaman Jenis Pohon dan Pola Penyebarannya pada Beberapa Wilayah Kawasan CA dan TWA Pananjung Pangandaran - Azuhra, Fatimah; Fatina, Ikfina Nawal; Hasna, Chumairo Nurul; Hanifiyah, Nur; Azizy, Maulana Khalil; Muliyah, Evi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
The Pananjung Pangandaran Nature Reserve (CA) and Recreational Park (TWA) are in-situ conservation areas that play an important role in preserving biodiversity, particularly lowland forest flora along the southern coast of West Java. However, these areas are increasingly subjected to anthropogenic pressures resulting from tourism activities and population growth, which may affect ecosystem stability. This study aimed to analyze tree species diversity, identify tree distribution patterns, and assess abiotic components within the CA and TWA of Pananjung Pangandaran. The research employed a quantitative descriptive method with an exploratory approach using the line transect technique at three observation stations, namely coastal forest and lowland forest areas within the CA, as well as lowland forest areas within the TWA. A total of nine observation plots measuring 20 × 20 m were established. The results showed that tree species diversity in the western coastal forest of the CA, the lowland forest of Ciborok Block in the TWA, and the lowland forest of Cikamal Block in the CA was categorized as moderate, with Shannon-Wiener diversity index (H’) values ranging from 1.029 to 1.742 and a uniform distribution pattern. Overall, each observation station exhibited a distinctive vegetation composition, resulting from varying interactions between biotic and abiotic components. Keywords: Tree Species Diversity, Tree Distribution Pattern, Shannon-Wiener Index, Nature Reserve, Recreational Park